2009
DOI: 10.1111/j.1525-1594.2008.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Review of Hemoglobin‐Vesicles as Artificial Oxygen Carriers

Abstract: Blood transfusion systems have greatly benefited human health and welfare. Nevertheless, some problems remain: infection, blood type mismatching, immunological response, short shelf life, and screening test costs. Blood substitutes have been under development for decades to overcome such problems. Plasma component substitutes have already been established: plasma expanders, electrolytes, and recombinant coagulant factors. Herein, we focus on the development of red blood cell (RBC) substitutes. Side effects hin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
100
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(101 citation statements)
references
References 25 publications
0
100
0
1
Order By: Relevance
“…Liposomal nanocapsules would be labeled with [ 18 F]fluorodeoxyglucose (11,12) or water-insoluble [ 18 F]fluorodipalmitin (13), although the labeling of liposome with these radioactive probes usually requires modification or reconstitution of its membrane. Furthermore, liposomal drugs are the products of multiple steps (4,5), requiring much longer process than the halflives of commonly used positron emitter nuclei, 11 C (20 min) or 18 F (108 min). Thus, labeling preformulated DDS drugs or substituting components of liposome is impractical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Liposomal nanocapsules would be labeled with [ 18 F]fluorodeoxyglucose (11,12) or water-insoluble [ 18 F]fluorodipalmitin (13), although the labeling of liposome with these radioactive probes usually requires modification or reconstitution of its membrane. Furthermore, liposomal drugs are the products of multiple steps (4,5), requiring much longer process than the halflives of commonly used positron emitter nuclei, 11 C (20 min) or 18 F (108 min). Thus, labeling preformulated DDS drugs or substituting components of liposome is impractical.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, human hemoglobin was encapsulated in liposome nanocapsule (liposome-encapsulated hemoglobin [LEH] to be an artificial oxygen carrier as a substitute for red blood cells (RBCs) (4,5). In order to clarify the behavior of LEH in vivo, noninvasive, real-time imaging of their movement is desirable.…”
mentioning
confidence: 99%
“…In an analogous approach, Djordjevich et al reported on encapsulation of Hb in micron and sub-micron size lipid vesicles (liposome-encapsulated Hb or LEH), with membrane made of phospholipids and cholesterol. 31,82-84 This design was to essentially mimic the physiological state of Hb in RBCs where it is encased within the cell membrane in a protected environment that preserved the suitable redox mechanisms for Hb function. A number of variations of this design followed, e.g., ‘neohemocytes’, ‘TRM-645 Neo Red Cells’ etc., where the primary focus was to maintain uniform Hb-encapsulation levels and uniform size distribution of the vesicles, prevent vesicle destabilization or fusion over time, and thereby enhance vesicle stability upon storage while maintaining the RBC-mimetic oxygen transport properties of the encapsulated Hb.…”
Section: B Rbc Substitutes and Oxygen Carrier Systemsmentioning
confidence: 99%
“…This effect could be supplemented by conjugation of the vesicle surface membrane with polyethylene glycol [56]. Moreover, PEG-conjugation seemed to enhance convective O 2 -transport at the site of microcirculation [22] and prevent the aggregation of Hb-liposomes in the plasma [66,87]. Another promising technique of encapsulation consists in the assembly of biodegradable nanocapsules (diameter less than 0.2 µm) made of polylactic acid.…”
Section: Liposome Encapsulated Hbmentioning
confidence: 97%